Malaysia enjoying full employment, says Ismail: I.L.0. criteria: Jobless rate down to 3pc, says deputy minister - News Straits, Times (New Straits Times, 2013)
Malaysia achieved full employment when the unemployment rate dropped to three percent in the second quarter of the year, the Dewan Negara was told. Deputy Human Resource Minister Datuk Ismail Abd Mutalib said based on International Labour Organisation standards, any country with an unemployment rate of less than four percent would be regarded as having attained full employment.